Prospecting for Groundwater Using the Continuous Vertical Electrical Sounding Method - Issah, Mohammed Mansuru; Aning, Akwasi Acheampong; Noye, Reginald Mensah; Mainoo, Patrick Amankwaa (European Scientific Journal, ESJ, 2018)
2-D CVES surveys using the Wenner configuration was carried out in 22 communities in the Tain District, Ghana. This was done with the objectives of assessing the subsurface geology, identify high groundwater potential zones for drilling high-yielding boreholes that could yield sustainable amount of groundwater. The collected resistivity data were converted from the apparent resistivity to 2-D modelsection using the least-square inversion algorithm with the help of Res2DInv software. The 2-D resistivity model-sections produced a high quality structural resolution leading to the demarcation of the layering of various lithological units, weathered layers and identification of important structures such as joints, fractures and faults. Quantitatively, it can be observed that all the drilled wet wells have aquifer zones between 30 m and 60 m within sandstone, siltstone and phyllite granitic environments. The result of the borehole drill logs revealed that the aquifers were within weathered and fractured zones and is in agreement with the models. The results showed that the boreholes yield within the study area varied between a minimum of 15 litres/min to a maximum 800 litres/min and the mean depth for intercepting aquifer was at about 30 m and below. The study revealed that the potential aquifer zones in the study area are mostly as a result of weathering of the overburden and fracturing of the underlying bedrock. The results suggest that the hydrogeology of the study area is highly complex since the development of groundwater is generally due to secondary porosities.